Analisis fungsi ganda plaza pada atribut jamaah salat di Masjid Agung Jawa Tengah - Hamdani, Ahmad Mahbub; Indrosaptono, Djoko; Sarjono, Agung Budi (Jurnal Arsitektur Lansekap; Vol.6, No.1, April 2020DO - 10.24843/JAL.2020.v06.i01.p11, 2020)
The Great Mosque of Central Java has an area called the plaza, namely Zone I, the Pillar area, and Zone II, the Payung Hidrolis Plaza Area. Preliminary observations by researchers showed that there was a suspicion related to the architectural settings of the plaza relating to the attributes of the congregation prayers, which were in the Great Mosque of Central Java. The method that will use in this research is the quantitative method using a descriptive approach. In this study, the independent variable is the perception of visitors in using the Central Java Grand Mosque plaza space with observational indicators of visitors' motivation, interests, and expectations. The dependent variable in this study is the hall attribute as a means of visitors to the main prayer room, which divided into two zones, namely: Zone I (alqonatir Pillar area) and Zone II (Hydro Payung Plaza Area). Field data collection was carried out on 300 respondents. Data collection was carried out for one week with division in 2 zones and two different times, namely afternoon and evening. Based on the results of research that has done that, there is a relationship between the function of the plaza of the Great Mosque of Central Java to the attributes of worshipers in Zone 1, Zone 2, Zone 1 and Zone 2.